2020
DOI: 10.26434/chemrxiv.11763555.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exposure to Mycotoxin-Mixtures via Breast Milk: An Ultra-Sensitive LC-MS/MS Biomonitoring Approach

Abstract: Exposure to natural food contaminants during infancy may influence health consequences later in life. Hence, breast milk may serve as a vehicle to transport these contaminants, including mycotoxins, from mothers to their infants. Analytical methods mostly focused on single exposures in the past, thus neglecting co-occurrences and mixture effects. Here, we present a highly sensitive multi-biomarker approach by a sophisticated combination of steps during sample preparation including QuEChERS extraction followed … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 10 publications
0
18
1
Order By: Relevance
“…In the former study, AME, BEA and OTA were the most frequently found toxins with concentrations up to 11, 12 and 68 ng/L, respectively (Braun et al unpublished; Ezekiel et al unpublished). EnnB and EnnB1 were detectable at lower concentrations (Braun et al 2018;Braun et al 2020b). In contrast to these results, high mycotoxin levels were reported by Rubert et al (2014) in breast milk obtained from Spanish mothers.…”
Section: Resultscontrasting
confidence: 84%
See 4 more Smart Citations
“…In the former study, AME, BEA and OTA were the most frequently found toxins with concentrations up to 11, 12 and 68 ng/L, respectively (Braun et al unpublished; Ezekiel et al unpublished). EnnB and EnnB1 were detectable at lower concentrations (Braun et al 2018;Braun et al 2020b). In contrast to these results, high mycotoxin levels were reported by Rubert et al (2014) in breast milk obtained from Spanish mothers.…”
Section: Resultscontrasting
confidence: 84%
“…EnnB and EnnB1 in two out of 21 samples at a mean concentration of 105,000 and 96,000 ng/L, respectively. In addition, ZEN was reported in 62% of the samples in a concentration range of 2,100 to 14,000 ng/L (Rubert et al 2014), whereas Austrian or Nigerian samples were not contaminated with ZEN (LOD 16 ng/L) (Braun et al 2020b). Hence, it is not unlikely that the Spanish study over-estimated exposure levels as no internal standards were applied.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations